Pengaruh Media Sosial dan Herding Behavior terhadap Keputusan Investasi Generasi Z di Kota Denpasar dengan Literasi Keuangan Sebagai Variabel Moderasi - Kadek Dellavia Vinata Prabandari; Ketut Tanti Kustina (Pusat Riset dan Inovasi Nasional, 2026)
This study titled “The Influence of Social Media and Herding Behavior on Investment Decisions of Generation Z in Denpasar City with Financial Literacy as a Moderating Variable” aims to analyze how social media and herding behavior affect investment decision-making among Generation Z in Denpasar City, and to examine the moderating role of financial literacy. This research employs a quantitative method, with data collected through questionnaires distributed to 100 respondents selected using purposive sampling. The respondents consist of Generation Z individuals who actively invest and use social media. The findings indicate that both social media and herding behavior have a significant positive influence on investment decisions. Furthermore, the moderation analysis reveals that financial literacy weakens the influence of social media and herding behavior on investment decisions among Generation Z. This study contributes to the understanding of how financial literacy can mitigate the impact of unverified information circulating on social media, and highlights the importance of financial education for younger generations to support more rational investment decision-making.